Advances in Education and Management International Symposium, ISAEBD 2011, Dalian, China, August 6-7, 2011, Proceedings, Part IV - Zhou, Mark.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This four-volume-set (CCIS 208, 209, 210, 211) constitutes the refereed proceedings of the International Symposium on Applied Economics, Business and Development, ISAEBD 2011, held in Dalian, China, in August 2011. The papers address issues related to Applied Economics, Business and Development and cover various research areas including Economics, Management, Education and its Applications.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer Science; Information Systems Applications (incl.Internet).; Artificial Intelligence (incl. Robotics).; Computer Communication Networks; Information Storage and Retrieval; e-Commerce/e-business.; Software Engineering